Tracking military maneuver training disturbance with low cost GPS devices - Denker, Phillip Michael (Kansas State University, 2013)
Military training lands are a vital resource for national security and provide crucial habitat for a number of threatened and endangered species. Military land managers must manage the land in accordance with federal environmental policy and regulation, while simultaneously providing the lands needed for training military forces. Off road maneuver training can cause significant environmental damage including removal of vegetation, compaction of soils, increased erosion, loss of habitat, and degradation of the landscape to a point of not being useful for continued military training. Various techniques have been developed to help the military land managers determine a sustainable training level for the landscape. Many of these techniques have limitations in the spatial resolution of data collected and the ability to provide timely and accurate assessments of training disturbance. Advancements in GPS and GIS technology over the past two decades have shown the potential to fill this knowledge gap. In this study low cost civilian off the shelf (COTS) GPS devices were accuracy tested to determine their capability to provide reliable and accurate military vehicle locations during training (1.93 m CEP, 4.625m 2dRMS). The GPS data collected from COTS devices on three battalion training exercises at Fort Riley, KS were processed in a GIS and statistically analyzed to compare and contrast several off road maneuver metrics (speed, turning radius, distance traveled) by vehicle type tracked, and by platoon in order to determine if units or vehicle types could reliably explain the variation in these metrics. Lastly, a method of mapping the relative environmental disturbance was developed and mapped for the same data sets. Wheel sinkage was used as a measure of disturbance, it was calculated at each GPS point based on vehicle type and soil conditions then mapped in using a fishnet grid for Fort Riley, Kansas.
Keywords: Global Positioning System; Maneuver; Military; Disturbance; Accuracy; Engineering, Agricultural (0539); Environmental management (0474); Geographic Information Science and Geodesy (0370)